Comparative evaluation between two hybrid local anesthetics in lower third molar extraction: A retrospective study - Sourav Kumar; Nayak Dipti; Kumar Shashank; Khan Musaab; Kumari Shalini; Chauhan Pranshu (SRM Journal of Research in Dental Sciences)
Background: Transalveolar extraction of the teeth may cause major serious complications, such as pain, swelling, and mouth opening. This study was conducted to find the most appropriate mixture of local anesthetics and glucocorticoids. Aims: This study was designed to compare pain, swelling, and mouth opening in 4% articaine with dexamethasone and 2% lignocaine and dexamethasone. Subjects and Methods: This retrospective study contains two groups with 30 patients in each group. Both the groups underwent transalveolar extraction, and 4% articaine + dexamethasone was administered in Group A, and 2% lignocaine + dexamethasone was given in Group B. Patients were assessed for pain, mouth opening, and swelling. Results: There was a better anesthetic effect with 4% articaine + dexamethasone (Group A) than with 2% lignocaine + dexamethasone (Group B); a significant finding was found in pain parameters but there was no significance in swelling and mouth opening. Conclusions: We found that 4% articaine + dexamethasone is superior for pain control intraoperatively, but no difference was found in mouth opening and swelling.